Targeted isolation of sulfur-containing metabolites from Lsr2-deletion mutant strain of Streptomyces roseosporus. Issue 60 (1st August 2017) - Deng, Lina; Wang, Rui; Wang, Guowei; Liu, Mingxu; Liao, Guojian; Liao, Zhihua; Chen, Min
Abstract : UPLC-QTOF-MS/MS targeted isolation of novel sulfur-containing metabolites, pyrismycins A–F, from a Lsr2 -deletion mutant strain of Streptomyces roseosporus . Abstract : Deletion of the Lsr2 gene in Streptomyces roseosporus up-regulated silent gene clusters and produced new secondary metabolites. An ultra-performance liquid chromatography quadrupole time of flight mass spectrometry (UPLC-QTOF-MS/MS) method was used to analyze metabolites of the mutant and wild-type strains, and recognize previously unreported sulfur-containing compounds based on their molecular formulas and fragmentation ions. The targeted isolation of unidentified compounds afforded six new sulfur-containing compounds, pyrismycins A–F (1–6 ), together with seven known analogues7–13 . Their cytotoxic effects were evaluated using four clinically relevant human cancer cell lines, gastric carcinoma SGC7901, breast carcinoma MDA-MB-231, lung carcinoma A549 and hepatocellular carcinoma HepG2. Compound7 exhibited the most potent cytotoxicity with IC50 values of 1.7, 5.8 and 6.3 μM against the SGC7901, HepG2 and MDA-MB-231, respectively.